Bioprospecção dos fungos endofíticos associados à espécie vegetal Eugenia jambolana e utilização de modificador epigenético no cultivo do fungo Lecythophora sp - Chapla, Vanessa Mara [UNESP] (2014)
The natural products have occuped an important role for humanity, in the use of folk medicine and in the generation of drug discovery. Endophytic fungi are microorganism that living in a mutualist association with host species, refleting benefits to both, and they are a promising source for natural products. The vegetal species Eugenia jambolana has been intensively explored chemically and biologically, because of its popular uses and it has several biological activities. In order to explore the potencionality of this plant species, E. jambolana was submitted to isolation of endophytic fungi in the leaves stems and fruits, of which thirteen endophytic fungi were isolated. The endophytes were cultived in small scale in Czapek (400 mL) to give the EtOAc crude extract. The EtOAc crude extract were submited to chemistry (thin layer chromatography, high performace liquid chromatography and 1H nuclear magnetic ressonance) and biological (antioxidant, antifungal, anticholinesterase and cytotoxic activities) analysis. All of crude extract showed at least one positive biological activity, which added the chemical analyzes allowed us to select two endophytic fungi to growing on a larger scale, and isolation of secondary metabolites. The endophytic fungus isolated from stems of E. jambolana encoded Ej-c3 was identified as Saccharicola sp. it was isolated 7 substances of which 4 are new (4-7). The substances 4 e 5 were inactive in the biological assays. Chemical study of Botryosphaeria parva (Ej-f1) isolated from leaves, was isolated 4 isocoumains [melein (3), 4-hidroxymelein (11), 5-hidroxymelein (13), 7-hidroxymelein (12)]. The substances 3 and 13 were active in antifungal assay agains the fungus C. sphaerospermum. In order to increase the metabolite production and activate the silent biossintetic pathway, the epigenetic appear as a useful and simple tool to gene expression. Lecythophora sp. an endolichenic fungus from Parmotrema tinctorum, was...